Investigation Of Mutagenic Effects Of Grayanotoxins II And III On Cultured Human Lymphocytes - Nurhan Cucer* and Recep Eroz (Al Ameen Medical College, 2010)
In order to detect the mutagenic effects of Gryanotoxins (GTX) II and III on human lymphocytes, two lymphocyte culture sets, one for micronuclei and other for chromosome analysis, were prepared. GTX-II and GTX-III at 3.52 mg/ml and 0.352 mg/ml concentrations were added to the lymphocyte cultures of ten female and ten male subjects by standard protocols. Then, the obtained data were compared with that of positive and negative control groups. Consequently, mean MN and chromosomal aberration values of twenty subjects were not considerably higher than those of negative control group (p >0.05). Only positive control group showed higher MN and chromosomal breakage values than the other groups (p <0.001). In conclusion, the usage of the GTX-II and GTX-III containing mad honey as a folk remedy may not cause chromosomal damage.